Making Archaeological Collections Available for Research: Recommendations for Repositories. Issue 3 (August 2019) - King, Julia A.; Samford, Patricia
Abstract: Archaeological collections repositories have two principal aims: preserving collections while also making them accessible. This accessibility is critical for the growing number of researchers turning to collections to study the past. This article describes steps that repositories can take to enhance access to collections in their custody, based on the experience of the Maryland Archaeological Conservation Laboratory, the state's public archaeological curation facility. These steps include the identification of stakeholders—archaeologists, Native American tribes, and stakeholder communities; creation of a detailed and prioritized collection inventory including artifacts and records; development of finding aids; reconstruction of provenience systems; and exploration of the digital delivery of collection information. For repositories ill equipped to hold archaeological collections, consideration should be given to transferring the collection to one with the appropriate resources and expertise. Abstract : Los repositorios de colecciones arqueológicas tienen dos objetivos principales: preservar las colecciones y al mismo tiempo hacerlas accesibles. Esta accesibilidad es crucial para el aumento de la cantidad de investigadores que están recurriendo a las colecciones para estudiar el pasado. Este artículo describe las pasos que los repositorios pueden dar para mejorar el acceso a las colecciones en su custodia. Estos pasos están basados en las experiencias del Laboratorio de conservación arqueológica de Maryland, el centro público de conservación arqueológica del estado, para hacer sus colecciones lo más accesibles posible. Estos pasos implican el reconocimiento de las partes interesadas incluyendo arqueólogos, tribus indígenas estadounidenses y las comunidades interesadas; la creación de un inventario detallado y jerarquizado de la colección que incluya los objetos y los expedientes, el desarrollo de los instrumentos de búsqueda, la reconstrucción de los sistemas de procedencia y la exploración de la difusión digital de la información de las colecciones. Para aquellos repositorios que no están adecuadamente preparados para albergar colecciones arqueológicas, se debe considerar la posibilidad de trasladar la colección al repositorio con los recursos y los conocimientos adecuados.